INCREASE IN INCOME TAX OF INDIVIDUALS THROUGH TAX AUDIT: INCREASE IN INCOME TAX OF INDIVIDUALS THROUGH TAX AUDIT - Asep Mulyana (Department of Accounting, Faculty of Economics, Universitas Nurtanio Bandung, 2023)
Taxes are the biggest income for the government in running the wheels of government, therefore citizens or here the public so that they can obey and comply with the obligation to pay taxes, therefore it is necessary to see from the income tax how it increases and it is necessary to examine the taxpayer so that the income tax increases. Increasing and according to the target every year with this inspection it is hoped that the public will be aware of paying taxes. This study aims to find out increasing individual income tax receipts through tax audits whether there is a big effect after conducting an examination of individuals. The method used in this study is a quantitative method. With a descriptive approach and the data used is secondary data. The results of the study show that partially it does not have a significant effect on Individual Income Tax Receipts. Through tax audits from the statistical results, it is necessary for tax officers to examine taxpayers to be more intense and always make taxpayers aware that taxes always increase from the results of examiners to do it regularly and continuously. Keywords: Tax, compliance, Personal Income Tax, Tax Audit